Airport System Control in Conditions of Continuous Random Processes of Traffic Flow - Usenik, Janez; Radačić, Željko; Jurum-Kipke, Jasna (Promet - Traffic&Transportation, 2012)
The article presents a systemic approach to air traffic op·eration and control in which the airport represents a basictechnical-technological and organisational system. Determiningoptimum control of the airport system therefore representsthe most important component in the process of controlling airtraffic system.